Co-location of Anganwadis to Primary Schools in India: A Conceptual Analysis - Rajesh, Anubha; Sharma, Monu Lal (THE PRIMARY TEACHER, 2025)
Numerous researches conducted in various countries using a wide range of methodologies indicate that the successful completion of pre-primary education is associated with school readiness and improved performance outcomes. Recognising this, the National Education Policy (NEP) 2020 has recommended a new education structure, 5+3+3+4, to provide seamless transitions for children. In the current scenario, four models of preprimary institutions delivering early childhood education are functional: (a) stand-alone Anganwadis, (b) Anganwadis co-located with primary schools, (c) pre-primary schools/ sections covering at least ages 5–6 years co-located with existing primary schools, and (d) stand-alone pre-schools (private or run by civil society organisations). Locating Anganwadi Centres (AWCs) on the premises of primary schools is intended to ensure universal enrollment, child preparedness for school, and a smooth transition to Grade 1 in primary school. This paper will focus on the concept of co-location, the steps taken by different states in India to implement the model, and its impact on the learning and pedagogical process during the early years. The paper will further discuss the advantages of co-locating pre-primary setups in primary schools and the challenges faced in this process. Finally, it will offer recommendations to facilitate the co-location process effectively. Understanding co-location involves examining how pre-primary institutions share resources and spaces with primary schools. This integration aims to enhance the educational experience for young children, making it easier for them to transition to formal schooling. Different states have adopted various approaches to implement this model, with some showing significant progress. The advantages of co-locating pre-primary setups in primary schools include better resource utilisation, increased enrollment rates, improved teacher collaboration, and a more cohesive educational experience for children. However, challenges such as infrastructural limitations, teacher training, and administrative coordination need to be addressed to maximise the benefits of this model.